Sawbones [large type] - Lenhardt, Melissa (Lenhardt, Melissa. Sawbones series., 2017)
Wrongfully accused of murder, Dr. Catherine Bennett is destined to hang... unless she can disappear. With the untamed territory of Colorado as her most likely refuge, she packs her physician's kit and heads West. But even with a new life and name, a female doctor with a bounty on her head can hide for only so long. --Amazon